Los riesgos de auditoria financiera y la planificación del control de inventarios y su influencia en los estados financieros - Zambrano Mochez, Roxana Beatriz (2015)
Inventory control begins with the application of rules , procedures and control policies to correct the shortcomings or risks in the Distribuidora Ariza is determined applying audit planning , based on information obtained by visiting the company, there is no good control of inventory management and this would cause us losses in the company. It is important to apply an audit companies because this way helps us go monitoring activities and responsible for each area to enhance both economic and financial situation of the company.